Genetic diversity in pearl millet restorers based on seed vigour traits and SSR markers (Bangladesh Journal of Botany, 2020)
Thirty four pearl millet restorer lines were evaluated on the basis of nine seed vigour traits and molecular analysis was done with 55 SSRs to study the genetic divergence among them. Cluster analysis based on seed vigour parameters revealed the considerable amount of variability and all genotypes were divided into six clusters. Furthermore, a set of 39 SSRs, selected after initial screening of 55, amplified 226 alleles with a mean of 5.84 alleles per locus. The highest polymorphic information content (PIC) value obtained was for PSMP 2084 (0.88) with a range of 0 to 0.88 and average PIC of 0.558. Neighbor joining tree based on molecular data differentiated all the genotypes into two major groups. The grouping based on both approaches can help breeders to use the studied material in further breeding for improvement of germination potential and early seedling vigour of pearl millet.